The Influence of The Work Environment on The Performance of Adminitratorats the LKSA Malikula'la Foundation - Mauladi, Ahmad; Makmur, Makmur (Jurnal Indonesia Sosial Sains, 2024)
The work environment is one of the important factors that can affect the performance of employees in an organization. A conducive work environment can increase productivity and job satisfaction, while a less supportive work environment can reduce motivation and performance. Knowing partial and simultaneous tests is the purpose of writing a study entitled The Influence of the Work Environment on the performance of Administrators at the Malikul A'la LKSA Foundation. The influence of the work environment on the performance of administrators at the LKSA Malikul a'la Foundation is the title of the research analyzed using quantitative methods with data collection techniques such as conservation and questionnaire distribution. This questionnaire was distributed to 20 people who were research samples at the LKSA Malikul a'la Foundation organization. The sampling uses a saturated sampling method. The data analysis used simple linear regression analysis. After this research process was carried out, the author found the results of the partial test showed that there was no significant influence between the work environment on management performance. While the test findings simultaneously show that the work environment has an influence on the performance of the board at the Malikul a'la LKSA Foundation.